Comparative biochemical and structural analysis of the flavin-binding dodecins from Streptomyces davaonensis and Streptomyces coelicolor reveals striking differences with regard to multimerization. Issue 10 (24th July 2019) - Bourdeaux, Florian; Ludwig, Petra; Paithankar, Karthik; Sander, Bodo; Essen, Lars-Oliver; Grininger, Martin; Mack, Matthias
Abstract : Dodecins are small flavin-binding proteins that are widespread amongst haloarchaeal and bacterial species. Haloarchaeal dodecins predominantly bind riboflavin, while bacterial dodecins have been reported to bind riboflavin-5′-phosphate, also called flavin mononucleotide (FMN), and the FMN derivative, flavin adenine dinucleotide (FAD). Dodecins form dodecameric complexes and represent buffer systems for cytoplasmic flavins. In this study, dodecins of the bacteria Streptomyces davaonensis (SdDod) and Streptomyces coelicolor (ScDod) were investigated. Both dodecins showed an unprecedented low affinity for riboflavin, FMN and FAD when compared to other bacterial dodecins. Significant binding of FMN and FAD occurred at relatively low temperatures and under acidic conditions. X-ray diffraction analyses of SdDod and ScDod revealed that the structures of both Streptomyces dodecins are highly similar, which explains their similar binding properties for FMN and FAD. In contrast, SdDod and ScDod showed very different properties with regard to the stability of their dodecameric complexes. Site-directed mutagenesis experiments revealed that a specific salt bridge (D10–K62) is responsible for this difference in stability.